Early urinary biomarkers of diabetic nephropathy in type 1 diabetes mellitus show involvement of kallikrein-kinin system - Vitova, Lenka; Tuma, Zdenek; Moravec, Jiri; Kvapil, Milan; Matejovic, Martin; Mares, Jan (BMC nephrology, 2017)
BACKGROUND: Additional urinary biomarkers for diabetic nephropathy (DN) are needed, providing early and reliable diagnosis and new insights into its mechanisms. Rigorous selection criteria and homogeneous study population may improve reproducibility of the proteomic approach. METHODS: Long-term type 1 diabetes patients without metabolic comorbidities were included, 11 with sustained microalbuminuria (MA) and 14 without MA (nMA). Morning urine proteins were precipitated and resolved by 2D electrophoresis. Principal component analysis (PCA) and Projection to latent structures discriminatory analysis (PLS-DA) were adopted to assess general data validity, to pick protein fractions for identification with mass spectrometry (MS), and to test predictive value of the resulting model. RESULTS: Proteins (n = 113) detected in more than 90% patients were considered representative. Unsupervised PCA showed excellent natural data clustering without outliers. Protein spots reaching Variable Importance in Projection score above 1 in PLS (n = 42) were subjected to MS, yielding 33 positive identifications. The PLS model rebuilt with these proteins achieved accurate classification of all patients (R2X = 0.553, R2Y = 0.953, Q2 = 0.947). Thus, multiple earlier recognized biomarkers of DN were confirmed and several putative new biomarkers suggested. Among them, the highest significance was met in kininogen-1. Its activation products detected in nMA patients exceeded by an order of magnitude the amount found in MA patients. CONCLUSIONS: Reducing metabolic complexity of the diseased and control groups by meticulous patients' selection allows to focus the biomarker search in DN. Suggested new biomarkers, particularly kininogen fragments, exhibit the highest degree of correlation with MA and substantiate validation in larger and more varied cohorts.
Keywords: dospělí; Female; diabetické nefropatie; biologické markery; albuminurie; Biomarkers; Adult; Nephrons; ženské pohlaví; Reproducibility of Results; lidé; Sensitivity and Specificity; Diabetic Nephropathies; senzitivita a specificita; Proteins; časná diagnóza; Humans; reprodukovatelnost výsledků; proteiny; Male; kalikrein-kininový systém; Albuminuria; Kallikrein-Kinin System; Early Diagnosis; mužské pohlaví; nefrony